Personnel Performance Analysis in Jayaraga Village, Garut Regency - Saylla Rahmawati Dewi; Aswin Palls; Arif Gumilar; Fikky Andrean Panjaitan; Desheila Alamanda; Fitri Risky Damayanti (Jurnal Restorasi : Hukum dan Politik, 2026)
The performance of village officials is the ability of employees to carry out their main duties and functions in accordance with their assigned responsibilities. This study aims to determine the Analysis of Employee Performance in Jayaraga Village, Garut Regency, as an effort to improve the quality of public administration services. The research method used is descriptive research with a qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used data reduction, data presentation, and conclusion drawing reinforced by triangulation techniques. This study uses Dwiyanto's (2008:50-51) performance theory, which includes five dimensions: productivity, service quality, responsiveness, responsibility, and accountability. The results of the study show that the performance of Jayaraga Village employees is generally good, as evidenced by fast, friendly, and procedurally compliant services, as well as accountability. However, several weaknesses were found, such as the formal recording of community complaints and community participation in financial supervision, which need to be improved to support future improvements in employee performance.